MATERNITY CAPITAL AS AN INNOVATIVE FORM OF SOCIAL FAMILY SUPPORT SERVICE - Tatiana I. Kapustina (Статистика и экономика, 2016)
The birth rate in Russia is growing, this year for the first time in twenty years the decline in the population may drop to zero. These changes are not enough to solve the demographic problem, but they are a deep character. What has influenced the dynamics of the introduction of such a new social protection instrument, as the maternity capital we try to explain in this article.